(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article explores the representation of women in American literature from the 18th century to the modern era. It analyzes how literary portrayals have reflected, reinforced, or challenged the social, political, and cultural roles assigned to women throughout U.S. history. By examining key texts and authors, the study identifies recurring themes such as domesticity, resistance, independence, and identity. This evolving literary image serves as both a mirror and a critique of gender norms in American society.